PERKAWINAN DI BAWAH UMUR MASYARAKAT 5.0 PERSPEKTIF FIQH MADZHAB SYAFI’I DAN UNDANG UNDANG PERKAWINAN DI INDONESIA - Alindi, Rizki Kila; Al Amin, Habibi (JURNAL HAKAM, 2023)
ABSTRACTLegal marriage is an absolute stipulation according to Islam. However, these noble intentions are often not in line with expectations if the husband and wife do not yet have maturity both physically and mentally. This unpreparedness can occur if it is caused by the intensity of children using gadgets in the 5.0 era. This journal will examine how the law of underage marriage in the community 5.0 is from the perspective of the Syafi'i madhhab fiqh, and how the relevance of the Syafi'i fiqh legal reasoning to the Marriage Law in Indonesia for underage marriages in the 5.0 community. The conclusion in this study is that the marriage law under the age of 5.0 according to the Syafi'i school is valid. By looking at the element of ability, namely prioritizing maslahah. The legal relevance of marriage under the age of 5.0 in the perspective of the Imam Syafi'i madhhab and the Marriage Law is the age limit. Where both clearly regulate the age limit for marriage. This correlation can be used for the concept of underage marriage in the community 5.0 and all deviations in it.Keywords: Underage Marriage, Shafi'i Madzhab Fiqh, Marriage Law. ABSTRAKPerkawinan yang sah merupakan ketetapan mutlak menurut agama Islam. Akan tetapi, niat mulia tersebut seringkali tidak sesuai dengan harapan apabila diantara pasangan suami isteri belum memiliki kedewasaan baik secara fisik maupun mental. Ketidaksiapan tersebut bisa terjadi apabila disebabkan oleh intensitas  anak-anak menggunakan gadget di era 5.0. Artikel ini akan mengkaji bagaimana hukum perkawinan di bawah umur masyarakat 5.0 perspektif fiqh madzhab Syafi’i, serta bagaimana relevansi nalar hukum fiqh madzhab Syafi’i terhadap Undang Undang Perkawinan di Indonesia terhadap perkawinan di bawah umur masyarakat 5.0. Kesimpulan dalam penelitian ini yakni hukum perkawinan di bawah umur masyarakat 5.0 menurut madzhab Syafi’i adalah sah. Dengan melihat  unsur kebolehan tersebut yakni mengutamakan maslahah. Relevansi hukum perkawinan di bawah umur masyarakat 5.0 dalam persepektif madzhab imam Syafi’i dan Undang Undang Perkawinan adalah pada batasan usia. Dimana keduanya mengatur secara jelas aturan batasan usia perkawinan. Korelasi tersebut dapat digunakan untuk konsep perkawinan di bawah umur masyarakat 5.0 dan segala penyimpangan di dalamnya.Kata Kunci: Perkawinan di Bawah Umur, Fiqh Madzhab Syafi’i, Undang --undang Perkawinan.